Zur älteren Talentwicklung beiderseits des Rheins zwischen Andernach und Bonn - Birkenhauer, Josef (ERDKUNDE, 1965)
The author starts by trying to reconstruct the earliest (Oligocene) land surface that it is possible to ascertain from Tertiary deposits (see profiles and map); he then proceeds to uncover the different stages in the development of the present drainage system. (a) There seems to have been an Oligocene valley (at a present height of 200-240 m.), running parallel to the present Rhine valley, but at a distance of about 6 miles farther to the west. This was filled up and the Oligocene relief was buried under river deposits in two stages: the first in the lower Miocene, reaching to a present level of about 360 m., and the second in the upper Miocene, reaching to a level of about 400 m. Dating is possible since volcanic activity coincided with the beginning of the first stage. (b) Superimposed on the flat Miocene surface, a new river began to excavate its bed, roughly along the course of the Oligocene valley and nearly reaching its bottom again; this is proved by well-rounded, typical Pliocene gravel (lower Pliocene). (c) Again the reversed process followed, filling the older relief up to the present, easily discernible, level of about 300 m. The process is documented by hardly or not at all rounded Pliocene gravel, reaching all the way up to the mentioned level (upper Pliocene). On this surface the river slid eastwards to its present course; through down-cutting during the Pleistocene it formed the nothern part of the Rhine gorge. (d) The facts mentioned support the view that the 300 m. surface is the most important for the development of the present drainage system within the Middle Rhine Highlands, since the present system must necessarily have originated on it. It can justly be termed the Pliocene and earliest true terrace of the Rhine. This and also the other well developed levels can be shown to have been of influence in shaping the valley lines of the tributaries in as much as they caused a small, but still perceptible fall in height where they cross them. There are no indications of any other Pliocene terraces between this one and the so-called main terrace (earliest Pleistocene), which are of any but local importance despite assertions to the contrary hitherto.